Efficacy of interventions to improve feeding difficulties in children with autism spectrum disorders: a systematic review and meta‐analysis. (25th June 2014) - Marshall, J.; Ware, R.; Ziviani, J.; Hill, R.J.; Dodrill, P.
Abstract Background Feeding difficulties are relatively common in children with autism spectrum disorders (ASD), but current evidence for their treatment is limited. This review systematically identifies, reviews and analyses the evidence for intervention in young children with ASD and feeding difficulties. Methods A comprehensive search strategy was used to identify studies from January 2000 to October 2013. Studies were included if they described interventions where the goal was to increase desirable eating behaviours or decrease undesirable eating behaviours using an experimental design, including single‐subject research methodology. Studies were reviewed for descriptive information, and research quality was appraised using a formal checklist. Individual study findings were compared using Improvement Rate Difference (IRD), a method for calculating effect size in single‐subject research. Results Overall, 23 papers were included. All studies reviewed had five or fewer participants, and reported on operant conditioning style intervention approaches, where the child is prompted to perform an action, and receives a contingent response. Where quality measures were not met, it was primarily due to lack of detail provided for the purposes of replication, or failure to meet social validity criteria. Meta‐analysis indicated a medium‐large effect size [mean = 0.69, 95% confidence interval (CI) 0.60 to 0.79] when the outcome measured was an increase in desirable behaviours (e.g. consuming food), but a small‐negligible effect size (mean = 0.39, 95% CI 0.18 to 0.60) when the outcome measured was a decrease in undesirable mealtime behaviours (e.g. tantrums). Only a small proportion of studies reported outcomes in terms of increased dietary variety rather than volume of food consumed. Conclusions The reviewed literature consisted primarily of low‐level evidence. Favourable intervention outcomes were observed in terms of increasing volume, but not necessarily variety of foods consumed in young children with ASD and feeding difficulties. Further research in the form of prospective randomized trials to further demonstrate experimental effect in this area is required.